Chemical modification of waste cooking oil to improve the physical and rheological properties of asphalt binder - Wan Azahar, Wan Nur Aifa; Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; Bujang, Mastura; Ngadi, Norzita (Elsevier, 2016)
The performance of asphalt binder modified with waste cooking oil (WCO) is affected by the quality of the WCO itself because of the degradation process during frying activity. The quality of WCO can be determined by conducting an acid value test, wherein an increased acid value has caused the decreasing of rheological performance. Therefore, untreated WCO with a high acid value is chemically modified and pre-treated with alkaline catalysts to undergo transesterification. The transesterification of WCO is performed as a pre-treatment to reduce high free fatty acid (FFA) content, which is equivalent to the acid value. The treated WCO sample undergoes a chemical test (acid value), physical test (penetration and softening test), and rheological test through a dynamic shear rheometer (DSR). The rheological performance of rutting, which is analyzed using DSR, is compared between the untreated and treated WCO to determine any improvement in rutting resistance after chemical modification. Results show that the acid value reduces from 1.65 mL/g to 0.54 mL/g after the chemical treatment of WCO. The decrease in acid value affects the improvement of penetration, softening point test, and rheological performance test, wherein increased failure temperature is achieved at 70 °C for treated WCO compared with the untreated WCO at 64 °C.